PROSPEK INDUSTRI GALANGAN KAPAL DALAM NEGERI GUNA MENGHADAPI PERSAINGAN GLOBAL - Aulia Windyandari (TEKNIK, 2008)
The development planning of maritime industry at the national level, the objectives, the vision, the mission,the strategy and the government policy that empower maritime industry potential is very important beimplemented effectively by all component of maritime industry, especially shipyard community inIndonesia. The main and strategic problems have to be solved immediately with the systematic plan. Thisarticle will be focused to the condition, contribution, challenge and prospect of shipbuilding industry tosupport maritime exploration program for the total development of maritime industry that able to competethe foreign shipbuilding industry.